Levantamento epidemiológico da doença periodontal nos trabalhadores rurais do polo citricultor do estado de Sergipe - Silva, Mairaira Teles Leão e (2015)
The chronic periodontal disease (CPD) is a degenerative infection, being the most important cause of tooth loss in adults. The occurence of the CPD is not uniform in populations due to changes in various risk factors. Periodontal diseases are the most common complications that happen and reoccur on adults stomatognathic, influencing directly in workers’ quality of life. The brazilian citrus production exhibits significant numbers, representing an important factor on the economic and social development of the region. Few are the studies related to the citrus workers population, besides the socioeconomic and educational adverses, they have difficult access to public health. Therefore, the aim of this study was to evaluate in a transversal way the prevalence, extent and severity of CPD in rural workers from 35 to 65 years old, involved in the orange culture from Lagarto and Salgado-SE. The data collected were done through questionnaires and full mouth periodontal examination. The sample was composed of 167 patients. The patients were classified according to the presence and severity of the CPD. The overall incidence of periodontitis was 86.8%, being distributed with 19.4%, 61.08% and 21.56% in its mild degrees (L), moderate (M) and severe (S) respectively. The male and the most disadvantaged socio-economic classes (D and E) were associated with CPD. Of the surveyed sites, 56.05% had bleeding on probing, 38.69% had clinical attachment loss (CAL) of up to 2 mm, 11.05% with CAL of up to 4mm. Patients with M and S grades had sites with mobility 2 and 3 measure. The incidence of CPD presented and its clinical markers is greatly increased compared to values reported in the literature, in part may be because it is a rural population and be vulnerable to external risk factors. This study demonstrates the importance of epidemiological studies involving populations of socio-economic risk. With these specific public policy studies can be instituted and monitored in these risk populations.